A Comparative case study on the experience of privatization in UK, Korea and Japan and implications to China SOES reform - Li, Xuan (KDI School, 2001)
This paper, first, reviews the theoretical framework of privatization with special concern over property rights and competitive nature of the market. It examines economic implication of property rights and suggests different policy implications under different market conditions. Through empirical studies of privatization in United Kingdom (UK), Japan, and Korea, it illustrates the gains from privatization. It also stresses the lessons learnt for future privatization process and policies. In addition, it reviews the recent Chinese reform programs including the ones of the state-owned-enterprises (SOE) and the financial sector. This paper argues that, without proper transfer of property rights, inefficiencies will remain and Chinese SOEs will continue to be a heavy burden on the national economy. Lastly, some policy suggestions for the future reform on the Chinese SOEs will be discussed.
Thesis(Master) --KDI School:Master of Public Policy,2001